Strategies for sustained collaboration between Zambian TEVET institutions and industry: Policy recommendations - Tembo, P.; Du Plessis, A. (South African Journal of Higher Education, 2025)
This article proposes strategies for sustaining collaborative activities between Zambian technical and vocational training (TEVET) institutions and industry. Research has established that collaboration between skills training institutions and industry is crucial in improving the quality of skills development. However, current collaborations lack adequate policy guidelines. As a result, skills training stakeholders describe the collaborations as unmeaningful. Data was collected from three training institutions offering craft certificate-level construction programs in three provinces. The study employed a hermeneutic-phenomenological approach underpinned by the social exchange theory (SET) to analyse collaborative activities. The study revealed factors that render the collaborations unmeaningful, such as a lack of commitment, unfair distribution of benefits and inadequate student funding. The analysis yielded several policy recommendations on sustaining collaborations between training institutions and industry. The study concluded that sustaining these will require mitigating institutional and industrial hindrances through policies. Among other strategies, these policies must include specific details regarding communication channels and procedures, compliance measures and benefits.